Dynamic kinematic assessment with 3D motion analysis after arthroscopic bankart repair: a mid- to long-term study - Hetto, Pit; Liewald, Raissa; Spranz, David Maximilian; Tsitlakidis, Stefanos (Journal of Clinical Medicine, 2025)
Background/Objectives: The aim of the study is to first evaluate mid- to long-term changes in shoulder range of motion (ROM) and functional performance in activities of daily living (ADLs) after arthroscopic Bankart repair using three-dimensional (3D) motion analysis. Methods: We prospectively analyzed five patients (mean age: 31.8 years) pre- and postoperatively at 8.4 months and eight patients retrospectively at 12.1 years (mean age: 40.4 years). Fifteen asymptomatic adults served as controls. Shoulder kinematics were assessed using the Heidelberg Upper Extremity (HUX) model during maximum ROM and four ADL tasks (apron, neck, wash, and book). Results: At short-term follow-up, forward flexion improved by 31° (p < 0.05) and abduction improved by 70° (p < 0.05), while other movements showed non-significant trends toward improvement. Long-term follow-up demonstrated sustained or increased gains in flexion (+9°) and abduction (+7°) but significant declines in external rotation (−5°) and internal rotation (−30°). ADL analyses showed significant postoperative gains in abduction/adduction during “apron” (+6.7°) and “neck” (+49.8°) tasks. The long-term results remained comparable to or better than postoperative values in most planes, although external/internal rotation during the “wash” task decreased over time. Compared with normative controls, patients employed a larger ROM during some ADLs, suggesting compensatory mechanisms. Conclusions: Arthroscopic Bankart repair yields sustained mid- to long-term improvements in shoulder ROM and ADL performance. Rotational deficits persist despite maintained flexion and abduction in the long run, underscoring the need for targeted rehabilitation strategies.
Veröffentlicht: 19. November 2025
Gesehen am 23.01.2026